The role of Saudi Universities in Achieving Intellectual Security for the Requirements of Sustainable Development, From the Viewpoint of the Faculty Members of Prince Sattam bin Abdulaziz University - Sharabi, Wedad Abdullah (Journal of Educational and Psychological Sciences, 2020)
The study aimed to clarify the concept of intellectual security, its importance in the stability of countries, and push it to advance, and reveal the cultural reality of universities, and the extent of this reality to face intellectual trends, from the viewpoint of faculty members at Prince Sattam bin Abdulaziz University. The research used the descriptive method using (the questionnaire) consisting of (40) paragraphs distributed on four axes; It was applied to a regular random sample of (582) faculty members at Prince Sattam bin Abdulaziz University, and the results revealed that: The results revealed that the axis of the role of universities in achieving intellectual security as a whole obtained an average of (3.33 out of 5) with an average (average) estimate On the level of fields, the requirements of sustainable development got the highest average (3.37), followed by the concept of intellectual security with an average of (3.33), thirdly, the dangers of Internet culture with an average of (3.31) and finally the suitability of university education for intellectual challenges with an average of (3.29) and all of them with an average rating (3.2). Based on the results, a number of recommendations and proposals were presented, the most important of which is the need to repeat research on intellectual security and its obstacles, and to trap deviant thought, and that care be taken to activate the anti-social resistance system.
Keywords: Intellectual security; sustainable development; Saudi universities